Recent advances in germanium nanocrystals: Synthesis, optical properties and applications. (October 2017) - Carolan, Darragh
Abstract: Germanium nanocrystals (Ge NCs) have recently attracted renewed scientific interest as environmentally friendlier alternatives to classical II–VI and IV–VI QDs containing toxic elements such as Hg, Cd and Pb. Importantly, Ge NCs are nontoxic, biocompatible, and electrochemically stable. An essential requirement is the ability to prepare Ge NCs with narrow size distributions and well characterized surface chemistry, as these define many of their photophysical properties. However, a thorough discussion on these criteria has not been achieved to date. Here, size, surface control, and mechanisms for light emission in Ge NCs are discussed and their exciting recent applications are highlighted. The beneficial properties of Ge NCs suggest that this material can improve the performance of numerous devices like solar cells, photodetectors, and lithium ion batteries.